O Exílio e o Reino: o filosófico e o literário no contista Albert Camus - Paiva, José Rodrigues de (Ciência & Trópico, 2011)
RESUMOAborda a obra de Albert Camus, situando-a entre o filosófico e o literário. Define os dois termos e, a partir deles, interpreta os contos da coletânea O exílio e o reino, apontando relações desses textos com outras obras do próprio Camus e de outros autores, tais como Franz Kafka, Thomas Mann, Herman Hesse, André Gide, bem como determinadas referências intertextuais. Destaca o simbolismo e o lirismo subjacente à escrita de Camus.ABSTRACTThe Exile and the Kingdom: The Philosophic and the Literary in the Story-teller Albert Camus. v. 24, n. 1, p. 111-123, jan./jun. 1996.Examines the work of Albert Camus, stressing his position between the philosophical and the literary approach. Delimitates the boundaries of that fields and, based on the especific meaning of each one, analyzes the short stories comprised in Camus’ book The Exile and the Kingdom, pointing out some relations between those texts and others Camus’ works, as well as others authors works, such as Franz Kafka, Thomas Mann, Herman Hesse, and André Gide’s. Examines some inter-textual references in those Camus’ short stories. Stresses the symbolistic and the lyrical aspects embeded in Camus’ wrightings.RÉSUMÉL’Exil et le Royaume:le philosophe et le littéraire chez Albert Camus. v. 24, n. 1, p. 111-123, jan./jun. 1996.Il analyse l’oeuvre de Camus et la situe entre le philosophique et le littéraire. Les deux termes sont définis et servent à l’interprétation des contes de l’anthologie L’exil et le royaume. Il établit des rapports entre ces textes et d’autres oeuvres de Camus et d’autres auteurs, tels que Franz Kafka, Thomas Mann, Hermann Hess, André Gide. Le symbolisme et le lyrisme trouvés dans les écrits de Camus sont mis en évidence.